Dual role of CD44 isoforms in ampullary adenocarcinoma: CD44s predicts poor prognosis in early cancer and CD44ν is an indicator for recurrence in advanced cancer. Issue 1 (December 2015) - Wu, Cheng-Lin; Chao, Ying-Jui; Yang, Ta-Ming; Chen, Yi-Ling; Chang, Kung-Chao; Hsu, Hui-Ping; Shan, Yan-Shen; Lai, Ming-Derg
Abstract Background Although postoperative adjuvant chemoradiotherapies prevent recurrence for some patients with ampullary cancer, the recurrence rate is as high as 29 % in patients with stage I cancer. In an effort to identify predictors of recurrence in patients with ampullary adenocarcinoma, we investigated the clinical value of assessing standard and variant forms of CD44. Methods Immunohistochemistry staining and reverse-transcription polymerase chain reaction (RT-PCR) was used to detect standard and variant forms of CD44 in samples of ampullary adenocarcinoma. The cDNA microarray analysis comparing tumors with or without pancreatic invasion was undertaken and analyzed by Ingenuity Pathway Analysis. Results The standard CD44 (CD44s) isoform was detected in 76 of 98 patients with ampullary adenocarcinoma, and the negative or weak expression of CD44s was correlated with pancreatic invasion, lymphovascular invasion, advanced stage and bone metastasis. Moderate to dense expression of CD44s was correlated with shorter overall survival in patients with localized cancer (T1 or T2 disease, P  = 0.0268). The patients with advanced cancer (T3 or T4 disease) and moderate or dense CD44s expression had a trend toward better survival. Alternative splicing of CD44 was confirmed using RT-PCR, which revealed that the CD44ν3-10 isoform was only expressed in patients with cancer recurrence. Fold change of CD44ν6-10 was also increased. In addition, networks containing CD44, vascular endothelial growth factor (VEGF), epidermal growth factor receptor (EGFR), transforming growth factor-β (TGF-β), matrix metalloproteinase 2 (MMP2), AKT, extracellular signal-regulated protein kinase 1 and 2 (ERK1/2), p38 MAPK, activated protein 1 (AP1)‚ and CTNNB1 were constructed after comparing microarray data from patients with and without pancreatic invasion. Conclusions Whereas CD44s functions as tumor-promoting oncoprotein in early localized ampullary adenocarcinoma, CD44 variants are expressed in advanced cancer and patients with recurrence. Regional invasiveness and distant metastasis of ampullary cancer is controlled by a complex interacting network.